Risk assessment for manual handling activities in a dairy industry - Muhammad Ruzairi, Khairulhafiy; Sukadarin, Ezrin Hani; Widia, Mirta; Alaman, A. (2023)
Workers in the dairy industry work in integrated plant facilities such as process hall, maintenance and utility, warehouse logistics, and quality checking. All workers are at risk for work-related injuries and job-related illnesses. This study aims to assess the ergonomic risk factor in manual handling activities in the dairy plant industry. Field observation and manual handling assessment charts (MAC) tool determined the ergonomic risk factor. The process hall department is the main sector where there are various areas from process raw receiving, raw storage, batching operations, and pasteurised storage to filling and packaging operations. The result found several hazards of manual activities, such as awkward posture, forceful exertion, repetitive motion, static posture, and contact stress. The highest score of ergonomic risk factor was found at the filling workstation during carrying weight load activities. Thus, controlling exposure to occupational hazards is the fundamental method of protecting workers